STRUCTURAL-TECTONIC FACTORS OF FORMATION OF KOROSTEN PLUTON’S TI-BEARING GABBROS - Remezova, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The papers deals with association of titanium-bearing gabbroidic intrusions with systems of faults of the Ukrainian shield the conclusion about leading hand of diagonal system of faults in formation of gabbroidic intrusions and the role of orthogonal system of faults in formation of massifs of latest generation and certain geochemical specialization of intrusion was noted.